GURU BERKARAKTER UNTUK PENDIDIKAN KARAKTER DI SEKOLAH - Suci Cahyati (Academy of Education Journal, 2020)
Character education is influenced by the teacher's character role. The teacher is a role model that is used as a role model and a real example for students in school and in the community. But the reality in the field shows that not all teachers are able to educate. This is shown from the rampant anmoral cases committed by teachers on students such as sexual harassment, physical violence, bullying, smoking in the school environment, and so forth. An immoral teacher can be a factor that affects the moral decline of the nation's children. Teachers should be able to character first in good character so they can set an example for students. Ki Hadjar Dewantara stated Ing Ngarsa Sung Tulada, Ing Madya Mangun Karsa, Tut Wuri Handayani. This term indicates that the teacher is an example that is very influential on the formation of character. How is the character that must be possessed by a teacher is an important question that needs to be answered by all educators. Teachers who have ideal character can contribute to the character education of students.